2009
DOI: 10.2478/v10078-09-0002-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tennis Match Data - New Acquisition Model

Abstract: The purpose of this research was to analyze and interpret the latent (factor) area of a tennis match. The entities in this research

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
(6 reference statements)
0
9
0
1
Order By: Relevance
“…Many researchers have sought to identify performance indicators that describe and explain effective players’ behaviours during the competition. In racket sports, points and error distribution allow to characterize players’ performance (i.e., profiling), predicting a match outcome and game success ( Djurovic et al, 2009 ; Katic et al, 2009 ; O’Donoghue, 2015; O’Donoghue and Ingram, 2001 ). Recently, Courel-Ibáñez et al (2015 ) examined winners and losers’ effectiveness from 15 games of top 16 male padel players, finding on average 44.3% of points (49.1% for winners) and 55.7% of errors (50.9% for winners).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have sought to identify performance indicators that describe and explain effective players’ behaviours during the competition. In racket sports, points and error distribution allow to characterize players’ performance (i.e., profiling), predicting a match outcome and game success ( Djurovic et al, 2009 ; Katic et al, 2009 ; O’Donoghue, 2015; O’Donoghue and Ingram, 2001 ). Recently, Courel-Ibáñez et al (2015 ) examined winners and losers’ effectiveness from 15 games of top 16 male padel players, finding on average 44.3% of points (49.1% for winners) and 55.7% of errors (50.9% for winners).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of tennis, many investigations have used observational methodology in the match and notational analysis to obtain information about aspects such as performance indicators (Djurovic et al, 2009; Katić et al, 2011; Cui et al, 2018), service effectiveness and returns (Gillet et al, 2009; Hizan et al, 2011; Martin et al, 2016), tactical aspects (Over and O'Donoghue, 2010; Cross and Pollard, 2011; Reid et al, 2016), or the displacements and the position of players on the tennis court (Martínez-Gallego et al, 2013; Pereira et al, 2017). Sometimes these data are downloaded directly from the official websites of the tournaments and in others, the researchers are the ones who perform the data collection through observation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Le Runigo et al (2005 , 2010 ) reported that advanced tennis players had shorter visual-motor delays than novices in an interception task with deviated trajectories, with typical values below 0.200 s. Carboch et al (2014 ) found that the response time of the returner in realistic conditions was longer than when using a ball machine. Fernandez-Fernandez et al (2008 ) in six returners measured the response time at between 0.161 and 0.237 s. Djurovic et al (2009 ) found non-significant differences between the forehand (0.132 ± 0.46 s) and backhand return of the serve (0.156 ± 0.51 s) and measured the longest response time in so-called reprogramming strokes (0.297 ± 0.121 s).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, they possess greater knowledge of situational probabilities or expectational information ( Katic et al, 2011 ; O’Donoghue, 2006 ). Djurovic et al (2009 ) found some differences between serve-return shots concerning the time of the occurrence of lateral racquet displacement, the amplitude of the racquet movement and the average latency time.…”
Section: Introductionmentioning
confidence: 99%